2018
DOI: 10.3168/jds.2018-14506
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation effects of pomegranate by-products on oxidative status, metabolic profile, and performance in transition dairy cows

Abstract: Recent studies demonstrated a high antioxidant capacity for pomegranate components due to their rich bioactive compounds, such as conjugated fatty acids and phenolics. The objective of the present study was, therefore, to assess whether pomegranate seed or pomegranate seed pulp (peel + seed) supplementation could be effective to improve antioxidant status, and hence metabolic profile and performance in periparturient dairy cows. After a 1-wk pretreatment period, Holstein cows (primiparous n = 12, multiparous n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 36 publications
10
37
1
Order By: Relevance
“…Our finding is consistent with Safari et al. (2018) who tested the dried pomegranate seed and peel in feeding dairy cows.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding is consistent with Safari et al. (2018) who tested the dried pomegranate seed and peel in feeding dairy cows.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports have shown that feeding dried pomegranate byproduct (Safari et al, 2018) F I G U R E 2 (A-E) Effect of pomegranate by-product silage on non-esterified fatty acids (NEFA), beta hydroxy butyric acid (BHBA), malondialdehyde (MDA), interleukin-1 (IL-1), and serum amyloid-A (SAA) at the different sampling time after parturition in Holstein dairy cows.…”
Section: Milk Productionmentioning
confidence: 99%
“…As such, results on both cell apoptosis and death and viability highlighted that PMG natural extract did not have a negative effect on BAEC physiology in culture. Previous studies have demonstrated the positive effect of PMG extract as feed supplement in different physiological phases, such as in postpartum Holstein cows under heat stress conditions (Khorsandi et al, 2019) and during the transition period (Safari et al, 2018). In particular, PMG supplementation improved ruminal fermentation (Khorsandi et al, 2019) and increased milk yield and milk composition (Abarghuei et al, 2013) in dairy cattle.…”
Section: Resultsmentioning
confidence: 99%
“…46 Pomegranate byproducts (eg, seeds, pulp, and peels) contain a potent source of polyphenols, predominantly flavonoids, phenolic acids, and tannins, as well as stereoisomers of vitamin E. Together, these compounds reduce reactive oxygen species and chelate metal ions to induce potentially beneficial immunomodulatory effects in ruminants. 49,94 Dairy calves supplemented with pomegranate extracts had increased in vitro synthesis of the lymphocyte-derived cytokines interferon-g and IL-4, as well as greater total immunoglobulin G (IgG), in response to ovalbumin vaccination. By improving aspects of both humoral and cell-mediated immunity, calves supplemented with polyphenols may have an improved immune response following vaccination.…”
Section: Phytonutrientsmentioning
confidence: 99%